The convergence of National Professional Qualifications in educational leadership and master's level study. Issue 4 (12th November 2018) - Lambert, Steve
Abstract : Purpose: In 2017 the UK Government decided that the suite of National Professional Qualifications (National Professional Qualifications for Middle Leadership, National Professional Qualifications for Senior Leadership and National Professional Qualifications for Headship) needs to be updated in order to ensure they remained relevant to the changing shape of the educational landscape, particularly through the expansion of multi-academy trusts (MATs). At the same time, the Government proposed a new National Professional Qualification for Executive Leadership aimed at the CEOs of MATs. The purpose of this paper is to explore the way in which the new National Professional Qualification (NPQ) programmes are having master's level criteria embedded into them to facilitate a seamless progression into the master's level study. Design/methodology/approach: The paper combines desk research with reflections on the experience of developing the new NPQ programme within higher education institutions (HEIs) and considers the implications of this upon current and emerging HEI practice and research into educational leadership. Findings: There were a number of key issues highlighted by the paper. Notably, the process of embedding academic criteria into a training programme, which was not used to support the notion of critical reflection. Also, the associated mechanisms of accreditation, existing professional networks and the upskilling of staff delivering the NPQ programme, and a professionally oriented interface between the university, employer and deliverer of the training. Originality/value: This paper provides an original perspective involving the embedding of master's level criteria into professional qualifications in the field of educational leadership.